"Jail not bail or bail not jail?" - Issues in judicial ethics - Roy, Jaytilak Guha; Mishra, Yatish (1995)
"Taking a closer look at the system of granting bail as provided in the Cr PC, the authors point out that the existing classification of bailable and non-bailable offences lack logical systematisation and that our courts while exercising discretion in this regard are increasingly failing to reflect judicial conscience of the community. They illustrate their viewpoint through discussing relevant recent cases"
Keywords: Legal ethics - India; Judicial corruption - India; Judiciary - India; Judiciary